Growth Response of Several Rubber Scion Clones to KNO3 and NPK Fertilisation - Usodri, Kresna Shifa; Gusta, Adryade Reshi; Widiyani, Dimas Prakoswo; Safitri, Novi; Aziz, Abdul (Biotropika: Journal of Tropical Biology, 2026)
This study investigated the growth responses of four rubber scion clones (GT 1, IRR 112, PB 260, and RRIC 100) to different fertiliser types and concentrations at Politeknik Negeri Lampung from August to December 2024. The experiment employed a factorial randomised complete block design with two factors: clone type (four levels) and fertiliser treatment (5% NPK, 10% NPK, 5% KNO?, and 10% KNO?). Growth parameters, including leaf number, chlorophyll content, branch number, and leaf whorl number, were measured 2 and 4 months after treatment. The results showed highly significant effects (P < 0.05) of clone type, fertiliser treatment, and their interaction on all measured parameters. Clone GT 1 consistently exhibited superior performance across all variables, with the combination of GT 1 and 10% NPK producing the highest values: 94.00 leaves, 66.25 SPAD units, 7.75 branches, and 62.00 whorls four months after treatment. The 10% NPK treatment significantly outperformed KNO? formulations across all clones, demonstrating the importance of balanced macronutrient nutrition, including phosphorus. The study concluded that GT 1 clone fertilised with 10% NPK solution represents the optimal combination for maximising scion production efficiency in rubber nursery systems, providing valuable guidance for clone-specific nutritional management strategies.